REDUNDANSI BAHASA RAGAM BERITA PERSPEKTIF STILISTIKA, SEMANTIK, ANALISIS WACANA, SOSIOLINGUISTIK - Umul Khasanah (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2010)
Abstract. This article explores the language use in newspaper columns. The principle of frugality, beauty, coherence, and language feature as language varieties should be considered in language use in newspaper columns.. Thus, various news can be studied from various approaches.   RBSK redundancy is treated differently by the stylistics, semantics, discourse analysis and sociolinguistics because of different language design orietantion of each field. Stylistics and semantics approach language use in expalanative descriptive point of views that results in regarding redundancy in RBSK as normal and acceptable. In contrast, discourse analysis and stylistics approach the language use in normative prescriptive point views that results in regarding redundancy in RBSK as mistakes should  be avoided. Key words: redundancy, news varietes, discourse analysis, sociolinguistics, semantics